Which pathologies of the penis can be diagnosed with computed tomography? A comprehensive approach to imaging findings - Aktürk, Yeliz; Soyer Güldoğan, Esra; Özbal Güneş, Serra (The European Research Journal, 2024)
Objectives: Since there are various benign and malignant diseases of the penis, different imaging methods can be used for diagnosis. Abdominal computed tomography (CT) is not a frequently used imaging method in diagnosing penile pathologies. In an abdominal CT scan performed with the standard technique, the slices are obtained by scanning from the diaphragm’s dome to the symphysis pubis’s lower edge. Although the whole penis is not always captured, almost all abdomen scans include a portion of the penis. Penile pathologies can be detected with careful evaluation by CT. Methods: In this study, we aim to investigate incidental penile pathologies detected in abdominal CT performed for other reasons and whether abdominal CT contributes to showing penile pathologies. Therefore, abdominal CTs of 3,698 male patients were re-evaluated for penile pathologies. Results: The mean age was 52.2 years. Of the CT scans, 38% were obtained due to trauma, 16% were taken for oncological causes, 16% for abdominal pain and acute abdominal pathologies, 10% for urological reasons, 20% for other causes. Penile pathology was detected in 33 (0.83%) of 3968 patients. The patients were divided into four groups according to the pathologies observed in the penis: Traumatic, inflammatory, tumoral, and other findings. Conclusion: Although CT is not routinely used to diagnose penile pathologies, it may be necessary if the whole penis is included in the examination.